2015
DOI: 10.1039/c5tc02080h
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in organic resistance memory with small molecules and inorganic–organic hybrid polymers as active elements

Abstract: The organic resistance memory has attracted a lot of attentions due to its high scalability, flexibility, easy processing, low fabrication cost, etc. Organic small molecules, which own well-defined structures and more accurate experimentsimulation matching, have been widely explored as the active materials for the application in organic resistance memory. In addition, inorganic-organic hybrid polymers have been expected to have charming resistive switching properties because they can potentially combine the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 101 publications
0
85
0
Order By: Relevance
“…The Pr-coordinated polymers (PFPh(BipyPr) n ) were prepared by coordination reaction with the Pr-free polymer and Pr triisopropoxide. The feed ratios of Pr complex in the polymers were 4, 6, 8 and 10 mol%, and the corresponding polymers were named PFPh(BipyPr) 4 , PFPh(BipyPr) 6 , PFPh(BipyPr) 8 , PFPh(BipyPr) 10 , respectively. of PFPh(Bipy) n ( Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pr-coordinated polymers (PFPh(BipyPr) n ) were prepared by coordination reaction with the Pr-free polymer and Pr triisopropoxide. The feed ratios of Pr complex in the polymers were 4, 6, 8 and 10 mol%, and the corresponding polymers were named PFPh(BipyPr) 4 , PFPh(BipyPr) 6 , PFPh(BipyPr) 8 , PFPh(BipyPr) 10 , respectively. of PFPh(Bipy) n ( Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…In the pioneering studies of polymer resistive memory devices, the doped or blended polymer systems, namely polymer composites, are oen used as the active materials. [6][7][8] Most recently, much attention have been paid to single polymer-based memory materials and devices, which can avoid the problem of phase separation and exhibit promising application for nextgeneration memory devices.…”
mentioning
confidence: 99%
“…Approach to practice of medicinal chemistry has developed from an empirical one involving synthesis of new organic compounds based on modification of chemical compounds of known biological activities could be better explored. It is well established that slight alteration in the structure of certain compounds are able to bring drastic changes to yield better drug with less toxicity to the host it observed that chemical modification not only alters physiochemical properties but also pharmacological properties 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They have known to exhibit diverse biological activities such as in vitro inhibition of cyclooxygenase and 5-lipoxygenase activities 3 . New acylated 5-thio-beta-D-glucopyranosylimino-disusbstituted 1,3,4-thiadiazoles prepared by cycloaddition of the glycosyl isothiocyanate with the reactive intermediates 1-aza-2-azoniaallene hexachloro antimonates, and have been tested in vitro antiviral activity against HIV-1, HIV-2, human cytomegallovirus (HMCV) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the design and synthesis of novel structures of intramolecular charge-transfer (ICT) compounds have attracted much attention due to their diverse applications in nonlinear optics (NLO) [1], organic photovoltaics [2-8], organic light-emitting diodes (OLEDs) [9], memory devices [10][11][12][13][14], field effect transistors (FETs) [15][16], and so on. ICT compounds normally have coexisted electron donor (D) and electron acceptor (A) moieties, which are connected together through conjugated linkers.…”
Section: Introductionmentioning
confidence: 99%